Size Matters: Arginine-Derived Peptides Targeting the PSMA Receptor Can Efficiently Complex but Not Transfect siRNA - Christopher N. Cultrara; Sunil Shah; Gina Antuono; Claudia J. Heller; Jorge A. Ramos; Uri Samuni; Jenny Zilberberg; David Sabatino (Elsevier, 2019)
Oligoarginine sequences conjugated to a short cancer-targeting peptide (CTP) selective for the prostate-specific membrane antigen (PSMA) receptor was developed for selective small interfering RNA (siRNA) delivery to a human metastatic/castration-resistant prostate cancer (PCa) cell line, which expresses PSMA on the surface. The PSMA-Rn (n = 6 and 9) peptides were synthesized by solid-phase peptide synthesis, characterized by liquid chromatography-mass spectrometry (LC-MS) and condensed with glucose-regulated protein (GRP)-silencing siRNAs. Native gels showed formation of stable CTP:siRNA ionic complexes. Furthermore, siRNA release was effected by heparin competition, supporting the peptides' capabilities to act as condensing and releasing agents. However, dynamic light scattering (DLS) and transmission electron microscopy (TEM) studies revealed large anionic complexes that were prone to aggregation and limited cell uptake for RNAi activity. Taken together, these data support the notion that the development of efficient peptide-based siRNA delivery systems is in part contingent on the formulation of discrete nanoparticles that can effectively condense and release siRNA in cells.